Internalisasi Nilai-Nilai Pendidikan Islam dalam Buku "Muslimah yang Diperdebatkan" Karya Kalis Mardiasih - Nafiah, Azizatun; Bakar, M. Yunus Abu (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2021)
Kalis Mardiasih is a pro-feminism woman who writes about the phenomena encountered in society particularly that occurred to a Muslima in her book â€œMuslimah Yang Diperdebatkanâ€. This book deals with many of the recent phenomena, including the use of hijab and social media abuses. Through literature study approaches, the values of Islamic education in the book are then aligned with concepts from different sources of literature. The function of Islamic education in addition to tauhid and worship another function of Islamic education is the founding of moral and social value to learners. The process of integrating value can be by sharing the activity like the cultivating of conduct. The roles of the various elements of Islamic education here are particularly influential in habituation, especially the roles of teachers and parents who are often directly involved with learners.